2019
DOI: 10.21037/tau.2019.06.22
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sperm DNA fragmentation index on assisted reproductive technology outcomes and its relationship with semen parameters and lifestyle

Abstract: Background: The sperm DNA fragmentation index (DFI) is widely regarded as a key measure for assessing male fertility, but the predictive value of the DFI for outcomes of assisted reproductive technology (ART) remains under debate. In this study, we used a large sample to analyze the effect of sperm DFI on pregnancy outcomes following ART and its relationship with oocyte fertilization and embryo development in in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI). We also explore the value of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 39 publications
12
78
6
Order By: Relevance
“…Telli et al also reported a negative correlation between DFI and sperm motility (r = − 0.267, p = 0.043) [38]. Yang et al reported a negative correlation between DFI and sperm motility, concentration, and morphology (r = − 0.307, − 0.552, and − 0.620, respectively; all p < 0.01) [11]. This study also revealed a positive correlation between DFI and age, suggesting that DFI increased as the patient aged.…”
Section: Prospective 8 Highmentioning
confidence: 93%
See 2 more Smart Citations
“…Telli et al also reported a negative correlation between DFI and sperm motility (r = − 0.267, p = 0.043) [38]. Yang et al reported a negative correlation between DFI and sperm motility, concentration, and morphology (r = − 0.307, − 0.552, and − 0.620, respectively; all p < 0.01) [11]. This study also revealed a positive correlation between DFI and age, suggesting that DFI increased as the patient aged.…”
Section: Prospective 8 Highmentioning
confidence: 93%
“…An explanation for the reduction in DNA fragmentation after varicocelectomy lies in the proposed pathophysiology of DNA damage in varicocele patients. Sperm DNA fragmentation occurs during spermatogenesis and sperm maturation [11]. Hypoxia caused due to venous stasis and reflux results in an increase in reactive oxygen species (ROS).…”
Section: Prospective 8 Highmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The %DFI can be used to assess sperm DNA damage and can be directly associated with fertility [26,40].…”
Section: Discussionmentioning
confidence: 99%
“…We did nevertheless observe single outlier measurements from several of the donors and a limitation of our study was that repeated analysis was only performed on eight donors. Repeated measurements on more individuals and linkage to changes in lifestyle are needed to establish if associations exist between lifestyle and the acrosomal status, as observed for some of the classical sperm parameters and sperm DNA fragmentation [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%